Technological support of workplace writing / Nurul Kamalia Yusuf - Yusuf, Nurul Kamalia (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Technology supported writing is crucial especially currently when digital transformation and innovation were rife. Previous studies in the field suggested that technology-enhanced learning became more widespread as writing tools that serve multiple purposes namely evaluation, scoring and instructional. In the present study, the needs for a certain components of writing instructions that are enabled by technological support were looked into. The study focuses on the perception of workers in different service sectors in Malaysia on technology-enhanced writing supports for their workplace writing in English needs. 46 operational level workers responded to the survey. Data were analysed quantitatively using Statistical Package for Social Science (SPSS) version 26, descriptive statistics. The findings revealed that most workers believed in the importance of digital support not only struggling second language writers but also as tools to assist them with the text-level focus (language) and genre focus. In conclusion, technology support serves as tools to assist the users with the structure and mapping the direction of their text, as well as mechanics in writing, grammar and spelling.